A review of sociological study on health and illness patterns in Kashmir - Sheikh, Manzoor Ahmad (Innovative Research Thoughts, 2017)
Health is a fundamental human right and is central to the concept of quality of life. Health care is a programme of services that should make available all facilities of healthcare and allied services necessary to promote and maintain the health of people. The contribution of health care institutions in the health care of an area can be assessed by its different components viz., number of doctors, availability of beds, infrastructure, paramedical staff, technical facilities etc. In India health care system is paralyzed because it has to face serous crises in coast, quality of care and equitable distribution of modes and standard services to the population as a whole. The idea of the social construction of the illness experience is based on the concept of reality as a social construction. In other words, there is no objective reality independent of our own perceptions of it. The social construction of the illness experience deals with such issues as the way some patients control the manner in which they reveal their disease and the lifestyle adaptations patients develop to cope with their illnesses.